Pengaruh Citra Merek, Harga Dan Gaya Hidup Terhadap Keputusan Pembelian Kopi Janji Jiwa Di Kota Karawang - Elita Rizki Damayanti; Eman Sulaeman (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of brand image, price, and lifestyle on purchasing decisions for coffee promises soul. Purchasing decision is one of the company's business goals that can have an impact on the continuity of the company's operations. The population used in this research is consumers who have purchased and used the product of Jiwa Jiwa coffee. The sampling technique used was accidental sampling method, with 100 respondents as a sample member. Data collection using a questionnaire. The analysis technique used in this study is multiple linear regression using the SPSS program. Instrument testing uses validity and reliability tests. The test results show that brand image has a significant effect on purchasing decisions, price has a significant effect on purchasing decisions, and lifestyle has no significant effect on purchasing decisions. Thus, it is expected that copy of the soul promise can maintain and improve quality and strategy in conformity with lifestyle, product quality, promotion and brand image because this has an influence on consumer purchasing decisions in making purchases.